Treating menopausal symptoms with a complex remedy or placebo: a randomized controlled trial - Hagens, Cornelia von; Schiller, Petra; Godbillon, Bettina; Osburg, Julia; Klose, Christina; Limprecht, Ronald; Strowitzki, Thomas (Climacteric, 2012)
Objective To evaluate the efficacy and safety of a complex remedy compared with placebo to treat menopausal symptoms.Methods A total of 102 peri- and postmenopausal women requiring treatment for menopausal symptoms were randomized to receive a complex anthroposophic remedy prepared in the homeopathic manner (Apis regina tota GL D4, Argentum metallicum D5, Ovaria bovis GL D4), 3 × 10 globuli daily (2 × 12 weeks) and placebo (12 weeks) in different orders of remedy (R) and placebo (P) (1: R/R/P, 2: P/R/R, 3: R/P/R). The primary endpoint was change in climacteric symptoms assessed by the Menopause Rating Scale II (MRS II) after 12 weeks. Secondary endpoints were changes of symptoms and safety throughout the study.Results Reduction of symptoms after 12 weeks did not differ between remedy and placebo (total score MRS II: -1.4, 95% confidence interval (CI) −2.8 to 0 vs. −2.3, 95% CI −4.4 to −0.3, p = 0.441) and had no clinical relevance (defined as reduction in MRS II ≥ −3.5). Comparison of secondary outcomes at 12 weeks between remedy and placebo or between groups after the 2nd or 3rd period compared to previous periods did not differ. Treatment with remedy for 24 consecutive weeks did not reach clinical relevance either. However, total reduction of symptoms after three periods in Group 1 (R/R/P) (−5.0, 95% CI −7.5 to −2.5) and Group 2 (P/R/R) (−5.9, 95% CI −8.7 to −3.1) reached clinical relevance whereas almost no decrease of symptoms after three periods was seen in Group 3 (R/P/R) (−0.5, 95% CI −2.9 to 1.9).Conclusions Treatment with the complex remedy for 12 or 24 weeks did not result in clinically significant improvement of menopausal symptoms.
Published online: 23 Oct 2011
Gesehen am 26.07.2018